Fabrication of a self-standing supramolecular membrane by a "soft spray" technique. Issue 28 (15th March 2023) - Jiao, Yonghua; Chen, Bingbing; Zhong, Chaofan; Hou, Xiaojiao; Fu, Yuanlin; Fan, Fuqiang; Wang, Tieqiang; Fu, Yu
Abstract : We report a one-step method to fabricate a free-standing supramolecular membrane composed of melamine and barbituric acid coordinated with silver nitrate (MBa-Ag) at the gas/liquid interface by a soft spray technique. Abstract : We report a one-step method to fabricate a free-standing supramolecular membrane composed of melamine and barbituric acid coordinated with silver nitrate (Mba–Ag) at the gas/liquid interface by a soft spray technique. MBa–Ag exhibits a folded two-dimensional layered morphology and thickness of 4.5 μm. The shortwave IR transmittance of MBa–Ag is as high as 95%, which is much higher than the transmittance of UV and visible light, and has the potential for electromagnetic wave transmission.